FC 102: Daily Phosphorus Intake, its Source and Mortality in Adults on Hemodialysis: The Diet-Hd Study. (3rd May 2022) - Su, Guobin; Saglimbene, Valeria; Bernier-Jean, Amélie; Wong, Germaine; Natale, Patrizia; Ruospo, Marinella; Craig, Jonathan; Hegbrant, Jorgen; Jesus Carrero, Juan; Strippoli, Giovanni
Abstract: BACKGROUND AND AIMS: Elevated serum phosphorus is associated with increased mortality in dialysis patients. Since the bioavailability of dietary phosphorus intake (DPI) varies based on its source and might contribute to serum phosphorus differently, the aim of the study is to investigate the association between total DPI and DPI from different sources with mortality in patients treated with hemodialysis. METHOD: DPI (plant, animal and other sources) was ascertained by the Global Allergy and Asthma European Network food frequency questionnaire within the DIET-HD study, a multinational cohort study of European and South American adults on maintenance hemodialysis. Adjusted Cox regression analyses were conducted to evaluate the association between total and source-specific DPI (both as tertiles and continuous in fraction or in absolute amount) with all-cause and cardiovascular mortality. RESULTS: A total of 8110 patients were followed for a median of 3.8 years (26 074 person-years). There were 2953 deaths, of which 1160 were cardiovascular-related. The median (interquartile range) DPI was 1388 (961–1994) mg/day, with only 12% (995/8110) of participants consuming the recommend range of DPI (800–1000 mg/day). Each standard deviation (SD, 896 mg/day) increase in total DPI was associated with higher all-cause mortality [hazard ratio (HR) 1.14; 95% confident interval (95% CI) 1.02–1.27] and cardiovascular mortality (1.45; 95% CI 1.08–1.96). Each SD (17%) increase in the fraction of DPI from plant sources was associated with lower all-cause mortality (HR 0.92; 95% CI 0.85–0.99) and marginally in cardiovascular mortality (HR 0.93; 95% CI 0.85–1.01). Each SD (9%) increase in the fraction of DPI from other source [HR: 1.06; 95%CI 1.02–1.10)] was associated with higher all-cause mortality. In contrast, each SD (17%) increase in the fraction of DPI from animal source was not associated either all-cause (HR: 1.02; 95% CI 0.96–1.07) or cardiovascular mortality (HR 1.07; 95% CI 0.98–1.16). Increased absolute amount of DPI from animal or other source were associated with both all-cause and cardiovascular mortality. CONCLUSION: A higher total DPI is associated with increased all-cause and cardiovascular death. This positive association is driven by the DPI from animal and other sources, while higher DPI fraction from plant associated with reduced all-cause mortality.